Phytochemical Evaluation and Bioactive Properties of Different Parts of Cassia occidentalis Plant Extracts - Ahmad, Irshad; Bashir, Kamran; Shair Mohammad, Imran; Wajid, Muhammad; Majid Aziz, Muhammad (Asian Journal of Chemistry, 2013)
The aim of this study is to investigate the secondary metabolites (bioactive constituents), antioxidant and enzyme inhibitory activities of the dichloromethane and methanolic extract of roots and aerial parts of the plant Cassia occidentalis which belongs to the family leguminosae. The extraction of coarse powder of dried roots and aerial parts of plant material was performed with dichloromethane and successively with methanol at room temperature. The filtrate was concentrated on rotary evaporator at 35 ºC. Then different phytochemical tests were performed for the identification of secondary metabolites, which revealed the presence of saponins, flavonoids, tannins, resins, anthraquinones and cardiac glycosides. The dichloromethane and methanolic extracts of Cassia occidentalis have bioactive secondary metabolites, significant free radical scavenging (antioxidant) and enzyme inhibitory activities such as chymotrypsin and lipoxygenase.